2000
DOI: 10.1002/(sici)1097-0266(200003)21:3<239::aid-smj97>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Formation processes of R&D consortia: which path to take? Where does it lead?

Abstract: Research into network formation generally takes one of two approaches. Either it examines the outcomes of variations in the context and motives of the formation without examining the dynamics of the process, or it identifies the sequence of activities during the formation but does not examine variations within the formation. In this paper we complement both approaches by examining variations within the formation process and their consequences. We take an exploratory approach. Our analysis of survey data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
248
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(272 citation statements)
references
References 69 publications
3
248
0
10
Order By: Relevance
“…Second, our findings are based on a single case in a specific context. The five episode types discerned here may be typical for multipartner alliances and networks in an innovation context, as the importance of interpersonal networks in R&D consortia is well established, and networks around technology ventures tend be based on embedded relations instead of arms-length relations (e.g., Doz et al 2000, Liebeskind et al 1996, Hite and Hesterly 2001. Yet similar interactions between interpersonal and interorganizational networks might also be found in other contexts that center on relatively autonomous professionals, who have to balance loyalty toward their organization with loyalties toward the community of peers and loyalty toward a shared idea, vision, or passion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our findings are based on a single case in a specific context. The five episode types discerned here may be typical for multipartner alliances and networks in an innovation context, as the importance of interpersonal networks in R&D consortia is well established, and networks around technology ventures tend be based on embedded relations instead of arms-length relations (e.g., Doz et al 2000, Liebeskind et al 1996, Hite and Hesterly 2001. Yet similar interactions between interpersonal and interorganizational networks might also be found in other contexts that center on relatively autonomous professionals, who have to balance loyalty toward their organization with loyalties toward the community of peers and loyalty toward a shared idea, vision, or passion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, endogenous network dynamics cannot explain how to access networks without having a prior position in them (Rosenkopf et al 2001). Indeed, process studies of organizational network dynamics found intentional network design alongside pathdependent network development mechanisms (Doz et al 2000, Koza and Lewin 1999, Sydow 2004). Firms and individuals may undertake strategic activities to sidestep structures that inhibit network transformation (Capaldo 2007, Rosenkopf et al 2001, proactively manage relationships through subsequent stages (D'Aunno and Zuckerman 1987, Jap and Anderson 2007), or steer relationship development iteratively, through learning and adaptation to changing conditions (Ariño and de la Torre 1998, Doz 1996, Kumar and Nti 1998, Ring and Van de Ven 1994.…”
Section: Dynamics In Interorganizational Networkmentioning
confidence: 99%
“…As a result, the 'linked scientists' perform the crucial role of reconciling the divergent modes of knowledge development in the academic and industrial environments and, consequently, of creating shared goals and objectives. The alignment of objectives and expectations is a key element for the network formation, since they allow the recognition of common interests and therefore the reasons to collaborate (DOZ;OLK;RING, 2000). According to Lam (2007), the 'linked scientists' are normally entrepreneurial professors, post-docs or doctorate students, who remain affiliated to the university but engage in some kind of relationship with firms -through joint projects (professors and post-docs) or funding (doctorate students).…”
Section: B) Research Career Structures and Work Normsmentioning
confidence: 99%
“…Doz, Olk and Ring (2000), for instance, have called them the "triggering entity". This paper does support the argument of Doz, Olk and Ring (2000), accepting that 'linked scientists' can work as "triggering entities". Bridging organisations, which stand between science and business, have also proved to perform such a role (i.e.…”
Section: Cross-case Analysismentioning
confidence: 99%
“…Alliance formation is the result of a complex process whose outcome is often the result of collaborative decision-making (Doz, Olk, & Ring, 2000;Yang, Lin, & Lin, 2010).…”
Section: Introductionmentioning
confidence: 99%